Spin dependent transmission of nickelocene-Cu contacts probed with shot noise - Mohr, Michael (2020)
The current I through nickelocene molecules and its noise are measured with a low-temperature scanning tunneling microscope on a Cu(100) substrate. Density functional theory calculations and many-body modeling are used to analyze the data. During contact formation, two types of current evolution are observed, namely an abrupt jump to contact and a smooth transition. These data along with conductance spectra (dI/dV) recorded deep in the contact range are interpreted in terms of a transition from a spin-1 to a spin-12 state that is Kondo-screened. Many-body calculations show that the smooth transition is also consistent with a renormalization of spin excitations of a spin-1 molecule by Kondo exchange coupling. The shot noise is significantly reduced compared to the Schottky value of 2eI. The noise can be described in the Landauer picture in terms of the spin polarization of the transmission of ≈35% through two degenerate dπ-orbitals of the nickelocene molecule.